Multivariate analysis of trip-chaining behavior - John V. Thomas; Robert Noland (European Regional Science Association (ERSA), 2005)
Trip-chaining behavior has generally been associated with various demographic characteristics of households and individuals. This includes households with children having more complex activity patterns, or those who are employed needing to conduct activities on the way to and from work because of time constraints. No studies, as yet, have controlled for other factors that might influence trip chaining behaviour, such as levels of urbanization, public transport availability, use of other transport modes, or various other local environmental factors. This paper explores these issues using both the 1995 Nationwide Personal Transportation Survey and the 2001 National Household Travel Survey. Both surveys have data on trip chaining behavior that allows multivariate analysis of individual level behavior. Various choice models are estimated, including ordered models that account for the number of chains in a trip. Results for both the 1995 and 2001 surveys are presented to examine potential changes in behavior over time.
Keywords: 330